Impact of long-term therapy with acetylsalicylic acid on immature platelet count: a single-centre cohort study. Issue 5 (May 2019) - Verdoia, Monica; Nardin, Matteo; Negro, Federica; Rolla, Roberta; Carriero, Alessandro; De Luca, Giuseppe
Abstract : N/A: Acetylsalicylic acid (ASA) represents one of the most widely used pharmacological treatments for the prevention of atherothrombotic events. However, its use in low-risk patients is still debated, due to the complex balance between benefits and bleeding complications, therefore requiring new tools for the assessment of cardiovascular risk. Immature platelet count (IPC) has been suggested as a marker of platelet reactivity and turnover, thus potentially reflecting the progression of the chronic atherothrombotic vascular damage, which could be prevented by ASA. However, no study has evaluated, so far, the impact of long-term therapy with ASA on the IPC among patients undergoing coronary angiography, which was the aim of the present study. We included patients from a single centre. Significant coronary artery disease (CAD) was defined as at least one-vessel stenosis more than 50%. Immature platelet fraction (IPF) levels were measured by routine blood cells count (a Sysmex XE-2100) in patients naive or chronically treated with ASA at admission. Among 1475 patients, 464 (31.5%) were ASA-naive. Patients on long-term antiplatelet therapy were more often men ( P  < 0.001), with a higher prevalence of cardiovascular risk factors and CAD. The mean levels of IPC did not differ between ASA-naive and treated patents (8 ± 5.3 vs. 7.8 ± 4.9, P  = 0.48). Similar results were obtained when considering IPC distribution across tertiles, as ASA therapy did not result as an independent predictor of IPC levels above the third tertile (≥8.6 × 10 6 /ml) [adjusted odds ratio (95% confidence interval) = 0.96 (0.63–1.48), P  = 0.87]. Results were confirmed in major higher risk subgroups of patients. The present study shows that among high-risk patients undergoing coronary angiography, the long-term therapy with ASA does not affect the levels of IPC.